ANALYSIS STRUCTURE OF BUILDING LOCAL GOVERNMENT 2 KARAWANG WITH CONCRETE STRUCTURE - Rio Supriyatna; Arief Firmanto (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
Desire to have a local government of Karawang office is quite magnificent service complete with adequate facilities that can support a variety of work activities of Government Officials and employees, it is the hope of the ideal and coveted by all circles. However, of course, in realizing a high desire that must be supported by substantial costs sourced from local revenue sources that in fact the people's money too, would be comparable and parallel with the level of service to thecommunity.However, fears as above hopefully not happen because the purpose 5th floor of building local government 2 Karawang certainly has a good purpose for increased imagery and public services for the people in the city's mayor. Thus will be realized an order of life is getting better with the presence of a complete service of policy makers in the Karawang City, which in turn will encourage improvements in the economy of the community.The building local government 2 using concrete structure. On the basis of the criteria safety and excellent service then loading the planning process should be in accordance with SNI-1727-2013 as well as the structural design of the building should refer to SNI-2847-2013 specification for structural steel buildings, other than that in the calculation of earthquake engineering should also refer to the SNI-1726-2012.Keyword : Analysis structure, Etabs, frame section, deflection.